Perancangan Desain Interior Arena Barongsai di Surabaya dengan Konsep Yin dan Yang - Poppy F. Nilasari, Yosan Probo Sarwono Martino Dwi Nugroho (Intra, 2014)
Lion dance wereÂ the Chinaâs origin sport and art who are now become the part of Indonesiaâs culture. Usually such as another sports and arts lion dance has a long historical background, roles in society life even in political and also true purpose in entertaining as well as educating us. So to represent the things mentioned above writer create the The Design Work of Lion Dance Arena on Surabaya. Hopefully, through this design can be a forum for lion dance lovers in East Java to pour their love of lion dance while preserving the cultural heritage of China and Indonesia.